Woman’s Leadership in Islamic Psychological Perspective - Muslim Hidayat; Putri Maulida Dwi Cahyani; Jihan Nurrizki Ahmadiyati; Nursyahdina Al-Rahmah Bobihu; Luluk Maknuna (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2022)
Essence of justice and gender equality cannot be separated from the context of society's understanding of the roles and place of men and women in the social realities of society. People still understand that gender is a cultural construct of roles, functions, and social responsibility between men and women. In general, beings in the women's world experience marginalization in both social and personal spheres. Alienation, injustice, and even ignoring women feel very common among men. The bad view of women throughout history has led to a bad view of all aspects of women. All religions, especially Islam, face new challenges. Islam is considered to perpetuate injustice and oppression of women, including patterns of male-female relationship (gender inequality). The problem, however, is that these gender inequalities stem either from religion itself, or from religious interpretations or understandings influenced by patriarchal traditions or cultures, capitalist ideologies or medieval Middle Eastern cultures. From the Islamic point of view, leadership is related to two basic social expectations or demands placed on leaders. The purpose of this study is to inform readers about the meaning of women's leadership, the challenges of leaders, and aspects of leadership by examining them from the perspective of Islam and Islamic psychology. The method used in this study is the use of a literacy research method, or commonly referred to as a literature study, and is sourced from data obtained by recording and processing the research data obtained.Keywords: Leadership, Woman, Islamic Psychological Perspective.